KALIMERHABA: SANALAĞDA TEMELLENEN TÜRK- YUNAN DOSTLUĞU - DURAL, Baran; GÜMÜŞ, Burak; SELÇUK, Mustafa (Atlas Journal, 2018)
The aim of this study is to analyze, whether existing bi-national Facebook online groups are capable of contributing to strengthen Greek-Turkish relations or not. Therefore some can tell Turks and Greeks separated from each other in the first quarter of 20.th century, may find a civil solution for themselves by getting help from facebook intersection groups, YouTube and other technological communication alternatives. If this interaction reaches a point when all political- social groups meet in some virtual groups and begin to debate in a mature way together, this new communication can force the ordinary citizens of both side to demand for better relationships.